Spatial Structure of The Leisure Zone In The Girsang Sipangan Bolon District Urban Waterfront (International Journal of Architecture and Urbanism, 2022)
Girsang Sipangan Bolon is one of the sub-districts under the administration of Simalungun Regency whose territory is partly directly adjacent to the shores of Lake Toba. The development concept of a waterfront culture for sustainable tourism is an importhing to do in this area. Tourism development that only relies on scenic beauty of the landscape will have difficult time to sustain for the future when there is degradation on environmental quality and boredom of visitors to the scenery presented. Identification of the spatial structure of Girsang Sipangan Bolon, morphology and circulation of the waterfront area and the typical type of development of the waterfront area are the objectives to be sought in this paper by using observation and geographic imaging of the area, whether are supports the concept of waterfront culture. Lack of open space to develop waterfront cultural activities, the morphology of the coastal area is not well planned where buildings with dense masses and heights block the view, and the area is more characterized by a recretional waterfront that relies more on the private sector. These characteristics are expected to provide more understanding and consideration for future development to emphasizing the concept of waterfront culture as an attraction and improving the morphology and circulation of the area that support sustainable waterfront tourism